Biomass-derived porous carbons for sorption of Volatile organic compounds (VOCs). (15th March 2023) - Shen, Yafei
Graphical abstract: Highlights: Progress and challenge of biomass-derived porous carbons for VOCs sorption was reviewed. Activation and modification mechanisms for preparation of porous carbons was discussed. Adsorption and desorption mechanism of VOCs onto porous carbons was concluded. Adsorption coupled with catalytic degradation of VOCs under ambient conditions were evaluated. Abstract: Volatile organic compounds (VOCs) can lead to environmental pollution and threaten human health due to their toxic and carcinogenic nature. The emission of VOCs increases dramatically with the accelerated industrialization and economic growth. Adsorption is identified as one of the most promising recovery technologies owing to its cost-effectiveness, flexible operation, and low energy consumption. In particular, adsorption-based technologies have a high potential to recycle both adsorbents and adsorbates, typically to capture valuable aromatic VOCs from industrial exhaust. Porous materials such as carbon-based materials, zeolite-based materials, and organic polymers and their composites have been extensively developed for VOCs adsorption focusing in adsorption capacity, hydrophobic property, thermal stability and regenerability. Among them, porous carbons as VOCs adsorbents have attracted increasingly attention, because they can be regulated by tuning the pore structure for VOCs accessibility during the adsorption process. Moreover, porous carbons can adsorb target VOCs by controlling the pore structure and surface functional groups. Significantly, the pore size distribution of porous carbons mostly controls the VOCs sorption process. Micropores provide the main adsorption sites, while mesopores enhance the diffusion of VOCs. In this review, the adsorption mechanism of VOCs onto porous carbons was generally concluded. Porous carbons can be designed as a specific structure for adsorption of aromatic VOCs by controlling the pore structure, hydrophobic sites, π-electronic structure, and surface functional groups. Since there are limited review literatures on porous carbons derived from renewable resources for VOCs adsorption, this paper will provide an overview on the synthesis of porous carbons from biomass and other organic wastes for VOCs adsorption or integrated oxidation processes (e.g., photocatalysis, non-thermal plasma catalysis, chemical catalysis) under ambient conditions with the objective of guiding future works on the VOCs abatement technologies towards a sustainable direction.